2019
DOI: 10.3168/jds.2018-15280
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of ginsenoside Rg1 on mastitis experimentally induced by lipopolysaccharide in lactating goats

Abstract: Escherichia coli is a cause of subclinical and clinical mastitis in dairy cattle and goats, and sometimes causes severe clinical disease that may result in death of the animal. Previous investigation showed that ginsenoside Rg1 extracted from Panax ginseng C.A. Meyer (Araliaceae) has an anti-inflammatory effect on the sepsis induced by E. coli lipopolysaccharide via competitive binding to toll-like receptor 4. We hypothesized that intravenous injection of Rg1 had therapeutic effect on mastitis experimentally i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Gram-negative bacteria, especially Escherichia coli ( E. coli ), are common pathogens of mastitis in ruminants [ 40 42 ]. LPS released from the bacterial cell wall causes a series of cellular immune responses, activating of inflammatory signaling, and producing of cytokines, and ROS [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gram-negative bacteria, especially Escherichia coli ( E. coli ), are common pathogens of mastitis in ruminants [ 40 42 ]. LPS released from the bacterial cell wall causes a series of cellular immune responses, activating of inflammatory signaling, and producing of cytokines, and ROS [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that G-Rg1 treatment reduced rectal temperature, udder skin temperature, udder circumference, and somatic count in milk. Moreover, it also enhanced the levels of milk production, lactose, white blood cells, and blood proteins (Wang et al, 2019). The addition of cultured wild ginseng root (CWGR) to goats' total mixed ration (TMR) increases plasma IgG and protein levels in organic Saanen dairy goats (Bae, 2016).…”
Section: Use Of Ginseng For Mastitis In Lactating Goatsmentioning
confidence: 99%